World agreement: innovations of national civil process law - Butryn-Boka, Nataliia; Chornyi, Andrii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The legal analysis of the institution of the settlement agreement in the wording of the new civil-procedural code was carried out, the theoretical and practical problems related to these legal relations were examined, the norms of the applicable civil procedural legislation were examined.